System and Software Development to Measure Cylindrical Pipes Based on Acoustic Reflectometry - Herrera Martínez, Marcelo; Gualtero Mosquera, Andrea; Rincón Flórez, Raúl Enrique (TECCIENCIA, 2013)
The following document describes the use of the acoustic reflectometry, the theory that follows it, and its implementation as a technique to measure cylindrical pipes. It describes how it was constructed and the materials used in the construction and implementation of the system that allows capturing signals (reflections) from the pipe under evaluation; also shown herein are the results obtained from measuring pipes of different lengths. This work also proposes simple application software that allows analyzing measurements made using acoustic reflectometry, as well as some conclusions and recommendations for future work.